Achieving protection against man-in-the-middle attack in HB family protocols implemented in RFID tags. Issue 3 (5th September 2016) - Aseeri, Aisha; Bamasag, Omaimah
Abstract : Purpose: In the past few years, HB-like protocols have gained much attention in the field of lightweight authentication protocols due to their efficient functioning and large potential applications in low-cost radio frequency identification tags, which are on the other side spreading so fast. However, most published HB protocols are vulnerable to man-in-the-middle attacks such as GRS or OOV attacks. The purpose of this research is to investigate security issues pertaining to HB-like protocols with an aim of improving their security and efficiency. Design/methodology/approach: In this paper, a new and secure variant of HB family protocols named HB-MP* is proposed and designed, using the techniques of random rotation. The security of the proposed protocol is proven using formal proofs. Also, a prototype of the protocol is implemented to check its applicability, test the security in implementation and to compare its performance with the most related protocol. Findings: The HB-MP* protocol is found secure against passive and active adversaries and is implementable within the tight resource constraints of today's EPC-type RFID tags. Accordingly, the HB-MP* protocol provides higher security than previous HB-like protocols without sacrificing performance. Originality/value: This paper proposes a new HB variant called HB-MP* that tries to be immune against the pre-mentioned attacks and at the same time keeping the simple structure. It will use only lightweight operations to randomize the rotation of the secret.